Indonesia’s Critical Minerals Diplomacy: Nickel Industrialization, Resource Nationalism, and Global Green Transition - Tegar Bintang Ramadhan (Artes Libres Institutum, 2025)
The accelerating global transition toward renewable energy has significantly increased demand for critical minerals, placing Indonesia at the center of international competition due to its vast nickel reserves. Indonesia's downstream industrialization policy represents a strategic shift from commodity export dependence toward value-added manufacturing and industrial sovereignty. Nevertheless, the political implications of this transformation remain insufficiently examined. This study investigates how Indonesia's nickel industrialization reshapes its diplomatic strategy, resource governance, and geopolitical positioning within the global green transition. Employing a political economy framework, the research combines qualitative policy analysis, trade statistics, investment data, and elite interviews involving government officials, industry representatives, and international stakeholders. The analysis demonstrates that Indonesia has successfully leveraged resource nationalism to attract strategic investments while strengthening its bargaining position within global battery and electric vehicle supply chains. However, the findings also reveal persistent governance challenges, including environmental degradation, unequal distribution of economic benefits, regulatory uncertainty, and increasing geopolitical competition among major powers. The article argues that Indonesia's critical minerals diplomacy reflects a broader transformation in development strategy that balances economic sovereignty, sustainable development, and international economic integration. Furthermore, the study contributes to debates concerning resource governance, industrial policy, and geopolitical competition by illustrating how emerging economies utilize critical mineral endowments to reshape international economic relations. The findings offer important policy implications for countries pursuing resource-based industrialization while simultaneously addressing sustainability and geopolitical risks associated with the global energy transition.